2018
DOI: 10.1038/s41541-018-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming immunogenicity issues of HIV p24 antigen by the use of innovative nanostructured lipid carriers as delivery systems: evidences in mice and non-human primates

Abstract: HIV is one of the deadliest pandemics of modern times, having already caused 35 million deaths around the world. Despite the huge efforts spent to develop treatments, the virus cannot yet be eradicated and continues to infect new people. Spread of the virus remains uncontrolled, thus exposing the worldwide population to HIV danger, due to the lack of efficient vaccines. The latest clinical trials describe the challenges associated with developing an effective prophylactic HIV vaccine. These immunological obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…In addition, particle size and viscosity of the core can be tuned, resulting in high payloads, controlled drug release and improved drug bioavailability to appropriate biological sites [13]. More recently, our lipid nanocarriers showed great potential as innovative delivery systems of protein antigens by chemical modification of the shell [14,15]. Far more complex than liposomes, our lipid nanocarriers are composed of a lipid core comprising a mixture of saturated and unsaturated glycerides, and a surfactant shell comprising a mixture of PEGylated surfactants and phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, particle size and viscosity of the core can be tuned, resulting in high payloads, controlled drug release and improved drug bioavailability to appropriate biological sites [13]. More recently, our lipid nanocarriers showed great potential as innovative delivery systems of protein antigens by chemical modification of the shell [14,15]. Far more complex than liposomes, our lipid nanocarriers are composed of a lipid core comprising a mixture of saturated and unsaturated glycerides, and a surfactant shell comprising a mixture of PEGylated surfactants and phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…Bayon et al, have also shown the capacity of nano-lipid complexes (NLC) to induce p24 specific immune responses against HIV in non-human primates (NHP). Four intradermal immunization over a period of 7 months showed that NLC-loaded p-24 antigen elicited significantly higher p24-specific antibodies as compared to the combination of free p24 antigen and CpG adjuvant [166] .…”
Section: Article In Pressmentioning
confidence: 97%
“…The use of 4DV3 as the targeting ligand resulted in enhanced endocytosis due to the uptake of 4DV3 functionalized nanocarriers combined with the allosteric interaction with CXCR4, suggesting that 4DV3 peptide could be considered as a dual function ligand. Bayon et al (2018) developed vaccine formulations comprising nanostructured lipid carriers (NLC) grafted with p24 antigen, together with cationic NLC optimized for the delivery of immunostimulant CpG, which was able notably enhance immune responses against p24 manifested in specific antibody production and T cell activation in mice as well as in nonhuman primates.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%